The Mass Attenuation Coefficients, Electronic, Atomic, and Molecular Cross Sections, Effective Atomic Numbers, and Electron Densities for Compounds of Some Biomedically Important Elements at 59.5 keV - Burcu Akça; Salih Z. Erzeneoğlu (Science and Technology of Nuclear Installations)
The mass attenuation coefficients for compounds of biomedically important some elements (Na, Mg, Al, Ca, and Fe) have been measured by using an extremely narrow collimated-beam transmission method in the energy 59.5 keV. Total electronic, atomic, and molecular cross sections, effective atomic numbers, and electron densities have been obtained by using these results. Gamma-rays of 241Am passed through compounds have been detected by a high-resolution Si(Li) detector and by using energy dispersive X-ray fluorescence spectrometer (EDXRF). Obtained results have been compared with theoretically calculated values of WinXCom and FFAST. The relative difference between the experimental and theoretical values are −9.4% to +11.9% with WinXCom and −11.8% to +11.7% FFAST. Results have been presented and discussed in this paper.